How Do Indonesian Listed Companies Disclose Information Related to Whistleblowing? - Rani, Utpala; Pramudyastuti, Octavia Lhaksmi; Nugraheni, Agustina Prativi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2022)
This study evaluates how Indonesian public listed companies (PLCs) facilitate whistleblowing and the extent to which they disclose its implementation through annual reports. Data were collected from 68 PLCs of Indonesian Stock Exchange (IDX). Using content analysis of annual reports and website analysis of the PLCs, this study found the companies prefer annual reports than website as the medium to disclose whistleblowing-related information. The disclosure of information on whistleblowing is relatively vary in depth and comprehensiveness. This study also indicated companies reluctance to enclose whistleblowing-related information though it has been obligated by the Indonesian Financial Services Authority (or Otoritas Jasa Keuangan/ OJK). Such reluctance can be associated with the absence of penalty for non-disclosers. This study revealed the interconnection between organization features and whistleblowing system. Thus, the companies do not provide fully information on whistleblowing system to prevent unintended consequences resulted from the disclosure and in turn, to indirectly unjustify the role of the whistleblowing system as a part of effective anti-corruption and anti-fraud strategy.